2023
DOI: 10.1088/2057-1976/acf581
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models to predict the relationship between printing parameters and tensile strength of 3D Poly (lactic acid) scaffolds for tissue engineering applications

Duygu Ege,
Seda Sertturk,
Berk Acarkan
et al.

Abstract: 3D printing is an effective method to prepare 3D scaffolds for tissue engineering applications. However, optimization of printing conditions to obtain suitable mechanical properties for various tissue engineering applications is costly and time consuming. To address this problem, in this study, scikit-learn Python machine learning library was used to apply four machine learning-based approaches which are ordinary least squares (OLS) linear regression, random forest (RF), light gradient Boost (LGBM) and extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Figure 2 shows that R 2 for the XGB model is 0.99 (~1). This is an excellent fit of the test values to the model trained by the training dataset [42]. R 2 for testing and training are also very similar, which shows that the model works similarly for training and testing data.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Figure 2 shows that R 2 for the XGB model is 0.99 (~1). This is an excellent fit of the test values to the model trained by the training dataset [42]. R 2 for testing and training are also very similar, which shows that the model works similarly for training and testing data.…”
Section: Resultsmentioning
confidence: 53%
“…Figure 2 shows that there is a degree of overfitting of the model for the dataset. Despite this, the RMSE and MAE values are quite low even for test data (MAE = 0.4, RMSE = 0.7); therefore, the model can still provide satisfactory knowledge for analyzing the importance of each factor and the mechanical behavior of the composites [42]. Figure 2c shows that SHAP values are positive for all the features.…”
Section: Resultsmentioning
confidence: 95%
“…Finally, the material and printing parameter optimization can be conducted considering not only shape fidelity but also the overall a priori performance of the construct from functional and biological perspectives [80,85,94]. For instance, Kondiah et al employed an ANN regression model to optimize the ink formulation based on the drug loading efficiency for a model drug in bone TE applications.…”
Section: For Pre-process Qcmentioning
confidence: 99%
“…According to Ahn et al [18], the raster orientation and air gap have a large effect on the tensile strength, while the bead width was found to have only a small influence. A recent study using machine learning (ML) models to predict relationships between printing process parameters and mechanical properties [46] found that larger infill densities (related to the air gap) have a positive effect on tensile strength, while higher printing speeds negatively affect this mechanical property. Furthermore, compressive strength was found to be unaffected.…”
Section: Characteristic Mechanical Propertiesmentioning
confidence: 99%